2014
DOI: 10.1186/2193-1801-3-532
|View full text |Cite
|
Sign up to set email alerts
|

Formulation of Trichoderma sp. SL2 inoculants using different carriers for soil treatment in rice seedling growth

Abstract: BackgroundTrichoderma sp. SL2 has been previously reported to enhance rice germination, vigour, growth and physiological characteristics. The use of Potato Dextrose Agar as carrier of Trichoderma sp. SL2 inoculant is not practical for field application due to its short shelf life and high cost. This study focuses on the use of corn and sugarcane bagasse as potential carriers for Trichoderma sp. SL2 inoculants.FindingsA completely randomized design was applied for this study. Trichoderma sp. SL2 suspension mixe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(19 citation statements)
references
References 15 publications
0
19
0
Order By: Relevance
“…Several isolates of Trichoderma has been found to enhance seedling development as it is considered an essential beneficial and biocontrol fungus [12]. A similar work was conducted by Doni et al [13] where the Trichoderma species isolated from corn tested for their potential rice germination and growth. Based on the rice seedling height as a growth parameter, there was a significant increase compared to control indicating that corn likely carries Trichoderma isolates with potential agricultural applications.…”
Section: Figurementioning
confidence: 84%
“…Several isolates of Trichoderma has been found to enhance seedling development as it is considered an essential beneficial and biocontrol fungus [12]. A similar work was conducted by Doni et al [13] where the Trichoderma species isolated from corn tested for their potential rice germination and growth. Based on the rice seedling height as a growth parameter, there was a significant increase compared to control indicating that corn likely carries Trichoderma isolates with potential agricultural applications.…”
Section: Figurementioning
confidence: 84%
“…Three promising Trichoderma isolates were further evaluated at different salinity levels in the pot trial under saline conditions. It was observed that seed biopriming with these plant growth promoting Trichoderma significantly promoted shoot, root, and other growth contributing parameters of maize at all salinity levels both under axenic and pot conditions [31]. Decrease in the shoot and root growth in saline water could be due to reduced photosynthesis and reduced root growth due to salinity and disturbance in mineral supply [32].…”
Section: Discussionmentioning
confidence: 98%
“…Availability of Trichoderma to the rice roots significantly enhanced root length and biomass yield and may be attributed to several growth promoting mechanisms like (i) mineral availability, (ii) availability of phytohormones, (iii) release of elicitors etc. ( Doni et al, 2014 ). Plant growth hormones like cytokinins-like molecules, e.g.…”
Section: Discussionmentioning
confidence: 99%